Demand, Supply and the Price Level in Macroeconomics - Rose, Hugh (Review of Economic Studies, 1952)
Journal Article Demand, Supply and the Price Level in Macroeconomics Get access Hugh Rose Hugh Rose Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 1, 1952, Pages 1–23, https://doi.org/10.2307/2296158 Published: 01 January 1952